An overview of polymeric dosage forms in buccal drug delivery: State of art, design of formulations and their in vivo performance evaluation - Fonseca-Santos, Bruno [UNESP]; Chorilli, Marlus [UNESP] (Elsevier, 2018)
Owing to the ease of the administration, the oral cavity is an attractive site for the delivery of drugs. The main difficulty for administration via the buccal route is an effective physiological removal mechanism of the oral cavity that takes way the formulation from the buccal site and decreases the bioavailability of drugs. The use of mucoadhesive polymers in buccal drug delivery shows assessing buccal drug permeation and absorption, however some studies bring an in vivo performance. This review points to the use of polymers in the manufacture of drug delivery systems (hydrogels, films and tablets) and shows the results of their in vivo performance tests.
Keywords: Buccal route; Drug delivery; Mucoadhesion; Pharmacodynamics; Pharmacokinetics; Polymers